PENGARUH PEMBERIAN METIL PREDNISOLON INJEKSI TERHADAP - Rosida, Yulia Rahmawati, Kukuh Judy Hand (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2016)
Methyl Prednisolone Injection is a type of corticosteroid drug with the works being categorized adrenokortikoid, anti-inflammatory and immunosuppressant . The purpose of this study was to determine the effect of Methyl prednisolone injection against dengue patient's recovery. This reseach was conducted in February in which the peak of endemic dengue. This reseach uses posttest design with the method of data collection is done by observation of secondary data, that is Methyl Prednisolone therapy injection of the patient's medical record and performed with the processing and tabulation system diagram and analysis using SPSS. From the 13 dengue patients were sampled study concluded that administration of Methyl Prednisolone injection affect total thrombosis and not affect temperature body of patient's recovery.Keywords : Methyl Prednisolone Injection, Total thrombosis, Temperature body, Dengue Patient’s